(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the psycholinguistic aspects of distance foreign language teaching to students of non-philological specializations. The study analyzes cognitive load theory, multimedia learning principles, speech production mechanisms, motivational and affective factors, metacognitive strategies, and multimodal information presentation in the context of online language education. The findings reveal that effective distance language teaching requires an integrated approach considering attention management, memory processes, psychological comfort, and the development of independent learning skills. Practical recommendations for designing instructional materials and creating psychologically supportive online learning environments are provided.